Evaluasi Berbasis WebQual terhadap Sistem Pelaporan Digital dalam Pendidikan - Herlina Sakka; Syafril Hidayat; Ramadiani (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
The rapid integration of digital reporting systems in education has transformed how schools manage academic data, yet user satisfaction remains a critical factor determining successful adoption. This study aimed to evaluate teacher satisfaction with the e-Rapor application at SMPN 5 Sangatta Utara using the WebQual framework, focusing on information quality, interaction quality, and usability. A quantitative descriptive approach was employed with a survey design involving all 35 teachers who used the application as respondents. Data were collected using an online questionnaire and analyzed descriptively to identify satisfaction levels and key areas for improvement. The findings indicate that information quality achieved the highest satisfaction score, showing that the application provides accurate, relevant, and easy-to-understand data. Usability also received a positive response but highlighted the need for more intuitive interface design and regular training, while interaction quality showed weaknesses in system responsiveness during simultaneous access and limited technical support. Overall, the study demonstrates that WebQual is an effective evaluation tool for assessing digital reporting systems and offers practical insights for improving educational technology implementation. This research contributes to the development of strategies for optimizing digital transformation in school administration and supports sustainable adoption of technology-based learning systems .